E-Wallet Payment Usage Among Young Consumers Using Technology Continuance Theory - Amron, Mohd Talmizie; Mohamad, Mohamad Amiruddin; Md Noh, Nur Hidayah (Information Management and Business Review, 2024)
Technological innovation has paved the way for the widespread adoption of e-wallets in Malaysia. This trend has been bolstered by government initiatives and incentives promoting cashless transactions. The study aims to contribute to the ongoing efforts to encourage cashless transactions and move towards a cashless society in Malaysia and beyond. The study collected data from 443 university students who had used e-wallets for payment transactions. The analysis examined the relationships between key constructs in the Technology Continuance Theory framework. The results revealed that a positive attitude towards e-wallets significantly influences students’ intention to continue using them. Additionally, perceived usefulness emerged as a crucial factor influencing students’ attitudes and overall satisfaction with e-wallets. However, the study did not find a significant relationship between perceived ease of use and attitude, suggesting that ease of use may not be a primary driver of students’ attitudes toward e-wallets. The theoretical implications of this study contribute to a deeper understanding of e-wallet adoption among the younger generation in higher learning institutions and provide valuable insights for the industry players. The practical implications offer guidance to key players in shaping e-wallet applications to meet the specific needs of university students, ultimately encouraging greater adoption and usage. Future research could explore additional variables and employ longitudinal studies for more comprehensive results.